Band structural and absorption characteristics of antimonene/bismuthene monolayer heterojunction calculated by first-principles - Zhan, Yanyan; Fang, Xuan; Wang, Dengkui; Fang, Dan; Li, Bobo; Li, Jinhua; Wang, Xiaohua (Frontiers in Chemistry, 2022)
The band gap of lateral heterojunctions (LHSs) can be continuously tuned by changing the widths of their components. In this work, Sb/Bi LHSs based on monolayer Sb and Bi atoms with armchair and zigzag interfaces are constructed, respectively. It exhibits an atoms number in planner dependent tunable band gap and near-infrared range absorption characteristics. And, they are systematically studied by first-principles calculations. The widths are represented by the numbers (n) of Sb or Bi atom chains. When n increases from 2 to 8, the band gaps of armchair Sbn/Bin LHSs decrease from 0.89 eV to 0.67 eV. And, the band gaps of zigzag Sbn/Bin LHSs decrease from 0.92 eV to 0.76 eV. The partial density of states (PDOS) spectra indicate that the occupied states of valence band are mainly provided by the Bi 6p orbitals. Additionally, the unoccupied states of conduction band are always provided by the Sb 5p orbitals and Bi 6p orbitals. For Sbn/Bin LHSs, the absorption edge along XX and YY direction move towards the long wavelength direction. These results provide an approach for the applications of two-dimensional materials in near-infrared devices.